A desorientação no acompanhamento terapêutico - Gerab, Cristiana Kehdi (2011)
The present research is based on a clinical case and its objective is to think about clinical Therapeutic Accompaniment (AT in Portuguese) by the transformation into narrative of what has been experienced between therapist and patient. The main questions that direct this work concern preoccupations experienced in the narrative fragments relating to the creation of the setting, the position of the therapist in transference and the tendency to a disorientation effect. It is not the purpose here to define AT from its history, nor to distinguish it from private or institutional clinical practice, nor to show the superiority of one over the other. This dissertation intends to consider the difficulties that this practice presents for the therapist, relating these to the basic foundations of psychoanalysis which refer to the creation and management of the setting. It is maintained here that the setting must be implicit in the therapist s body. From this central idea, it is possible to develop elements that allow us to think about an expansion of this clinical practice in difficult cases, and about the disorientation experienced by the therapist